Smart pultruded composite reinforcements incorporating fiber optic sensors - Kalamkarov, Alexander L.; Fitzgerald, Stephen B.; Georgiades, Tasos (My University, 1998)
The issues of processing, evaluation, experimental testing, and modelling of smart fiber reinforced polymer (FRP) composite materials are discussed. The specific application in view is the use of smart composite reinforcements for a monitoring of innovative bridges and structures. The pultrusion technology for the fabrication of fiber reinforced polymer composites with embedded fiber optic sensors (Fabry Perot and Bragg Grating) is developed. The optical sensor/composite material interaction is studied. The tensile and shear properties of the pultruded carbon/vinylester and glass/vinylester rods with and without optical fibers are determined. The microstructural analysis of the smart pultruded FRP is carried out. The interfaces between the resin matrix and the acrylate and polyimide coated optical fibers are examined and interpreted in terms of the coating's ability to resist high temperature and its compatibility with resin matrix. The strain monitoring during the pultrusion of composite parts using the embedded fiber optic sensors was performed. The strain readings from the sensors and the extensometer were compared in mechanical tensile tests.
Keywords: Optical fiber detectors; Pultrusion; Fiber-reinforced plastics; Polyimides